Parenting under Pressure: The Impact of Socioeconomic and Environmental Stressors on Family Stability and Child Development - Baharudin, Haiza Hayati (Darul Yasin Al Sys, 2025)
Rising concerns over public safety, financial instability, and housing insecurity are making parenting increasingly difficult in today’s socio-economic climate. This essay explores how these challenges impact both parents and children, exacerbating long-term developmental and social issues. Parents are struggling to meet their children's basic needs amid rising living costs, stagnant wages, and unpredictable job markets. Unstable housing and frequent relocations disrupt children's social development, emotional stability, and academic performance. These findings are supported by the latest economic and social data. In communities marked by crime, drugs, and violence, children face additional barriers to safe recreation and positive peer interaction. Overly cautious or rigid parenting, often a response to unsafe environments, can impair children's social and problem-solving abilities. Chronic parental stress—often tied to financial hardship—is associated with inconsistent discipline, mental health challenges, and neglectful conditions such as hypothermia. For children, this results in increased anxiety, emotional instability, developmental delays, and compromised physical and mental health. These cumulative factors contribute to a cycle of generational poverty and trauma, significantly impairing children's long-term cognitive development, school readiness, and well-being. To address these issues, the second part of the essay proposes a range of research-informed interventions suitable for students from diverse academic backgrounds. Recommendations include funding programs focused on personal safety education, establishing secure community centers, offering child care subsidies, improving access to affordable housing, and providing financial literacy training. The essay concludes by positioning stable parenting not only as a private concern but as a critical public investment. It calls for coordinated efforts among schools, community organizations, healthcare providers, and government agencies to break the intergenerational cycle of disadvantage and secure a more equitable future for all children.